Designing a Model of Audit Quality Based on Various Organizational Culture Factors - Abbas Ali Daryaei; Vahid Shahbazi (بررسی‌های حسابداری و حسابرسی)
Objective Auditing is a very important and respected profession that should render precise and quality information to win the public's trust in society. This study seeks to develop a model for audit quality considering the components of organizational culture. Methods A mixed-methods design was employed. In the qualitative phase, open, semi-structured interviews were conducted with 17 auditing experts and academics. In the quantitative phase, the sample consisted of 106 managers and employees from audit firms, providing services to companies listed on the Tehran Stock Exchange. Following the grounded theory, qualitative data obtained from the interviews were analyzed through open, axial, and selective coding in the MAXQDA. Finally, an audit quality model was developed based on the components of organizational culture with 15 axial codes and 85 themes. This model was fitted using structural equation modeling in SmartPLS. Results According to the results of this study and the proposed model, the components of organizational culture that affect audit quality include empowerment, control and supervision, innovation and risk-taking, organizational ethics, communication management, group culture, cooperation culture, competitive culture, fundamental values, organizational vision and mission, attention to stakeholders, organizational goals and objectives, organizational excellence, organizational adaptability. Therefore, culture significantly influences the mechanisms driving audit quality, thus highlighting the imperative for audit firms to enhance their cultural practices.